PENGARUH TERTIB ADMINISTRASI KEARSIPAN DAN PROFESIONALISME PEGAWAI TERHADAP PENINGKATAN KUALITAS TARUNA DAN TARUNI PADA JURUSAN MANAJEMEN SEKOLAH TINGGI PENERBANGAN INDONESIA CURUG TANGERANG - Satiti Utami (Politeknik Penerbangan Indonesia Curug, 2021)
This study aims to determine the influence of the good filing system and professionalism of employees together to improve the quality of student services at the Departement of aviation Management Departement STPI Curug Tangerang.The subjects were students STPI Aviation Management Department. Data were obtained from questionnaires distributed to 65 respondents from a population of 183 people.Research shows that the good filing system and professionalism of employees together have a positive and significant impact on improving the quality of student services at the Department of aviation Management STPI, it can be seen from the remaining 22,56% influenced by other factors carefelly and not analyzed further in this study.